Udział gmin w podatkach państwowych - uwarunkowania prawne i kierunki zmian - Brol, Marcin (Communes share in the national income taxes - legal aspects and the course of changes, 2006)
One ofthe most important sources of income in Polish communes is the share in the income taxes. In the recent years the importance of this source has grown significantly. This paper shows some legal aspects of this problem. It also describes shaping of incomes in some ofthe communes ofthe Lower Silesia region. This study is funded by the Committee of Scientific Research (grant no I H02C 091 26).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 195-198